Study on SOD1 GENE +35A>C polymorphism in impaired glucose regulation patients of Bangladeshi origin - Shahriar, S.M. (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.